2016
DOI: 10.1111/cea.12809
|View full text |Cite
|
Sign up to set email alerts
|

Raised interferon‐β, type 3 interferon and interferon‐stimulated genes – evidence of innate immune activation in neutrophilic asthma

Abstract: Running TitleRaised interferons β and λ in neutrophilic asthma Accepted ArticleThis article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 50 publications
(73 reference statements)
2
30
0
Order By: Relevance
“… 45 On the other hand, a significant heterogeneity of asthma may involve different inflammatory phenotypes, some of which may differ in terms of innate immune activation during viral infection. 46 Our observations documenting impaired IFN responses to viral infection in a subpopulation of asthma patients are in line with well-established non-atopic asthma phenotype, which includes respiratory infections as dominant exacerbation-triggering factors. 47 A recent systematic review documented association of non-atopic asthma/wheeze with lower respiratory tract infections in children and adolescents.…”
Section: Discussionsupporting
confidence: 87%
“… 45 On the other hand, a significant heterogeneity of asthma may involve different inflammatory phenotypes, some of which may differ in terms of innate immune activation during viral infection. 46 Our observations documenting impaired IFN responses to viral infection in a subpopulation of asthma patients are in line with well-established non-atopic asthma phenotype, which includes respiratory infections as dominant exacerbation-triggering factors. 47 A recent systematic review documented association of non-atopic asthma/wheeze with lower respiratory tract infections in children and adolescents.…”
Section: Discussionsupporting
confidence: 87%
“…Neutrophil functions are crucial in clearing bacterial infections and wound repair (175,176). A major target of the effects of IFN-λs may be neutrophils (62,177). A study by Blazek et al showed that in a collagen-induced arthritis model, IFNL1 showed anti-inflammatory function by reducing the numbers of IL17producing Th17 cells and the recruitment of IL-1b expressing neutrophils, which is important to amplify the inflammatory process (62).…”
Section: Bacterial Infectionsmentioning
confidence: 99%
“…However, rhinovirus-induced interferon production in hBECs is not deficient in well-controlled asthma (Sykes et al, 2014), hBECs from asthmatics have preserved interferon responses to influenza and respiratory syncytial virus (RSV) (Patel et al, 2014), and TLR responses are not impaired in asthmatic airway and blood cells (Sykes et al, 2013). In addition, robust IFN-γ and IFN-λ responses have been found clinically in children with asthma during naturally-occurring virus-induced exacerbations (Lewis et al, 2012, Miller et al, 2012), and severe adult asthmatics and neutrophilic asthmatics have recently been shown to have a dominant IFN-γ immune response in BAL (Raundhal et al, 2015, da Silva et al, 2017). …”
Section: Introductionmentioning
confidence: 99%